Phenological Study of Trees in Arunachal Pradesh - Beniwal, B. S. (Indian Forester, 1987)
Phenological study is very important for timely seed collection, raising of nursery and plantations. This study was taken up in Arunachal Pradesh in 1979 and was confinued Upto 1984. The total 88 specie. Were observed in six centres which were located in tropical, subtropical and temperate zones. Out of 88 species, 11 were conifers and the rest broad-leaved species. It was observed that maximum number of species (21 out of 88) flower during March and minimum in the months of January (2 species), October and December (1 species in each month) whereas, fruit of maximum species (13 species out of 88) ripe in the month of December and minimum species (1 species) fruit in the month of January. It was also oberrved that in North-Western part of Arunachal Pradesh, the emergence of new leaves, leaf-falling, flowering and fruitlng is earlier by 10.15 days compared to North-Eastern part. This might be due to comparatively more humidity and less temperature in the North-Eastern part of Arunachal Pradesh. Further, It was also observed that pbenological phenomena varies from year 10 year depending upon humidity and temperature. Leafing and flowering are advanced due to early rains and high temperature and Vice-versa, whereas, fruiting is delayed by rains and advanced due to high temperature and drought. Leaf fall is delayed due to rains and high temperature and advanced due to drought and low temperature.